2021
DOI: 10.1152/japplphysiol.00342.2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error of self-paced exercise performance in athletic women is not affected by ovulatory status or ambient environment

Abstract: Measurement error(s) of exercise tests for women are severely lacking in the literature. The purpose of this investigation was to 1) determine whether ovulatory status or ambient environment were moderating variables when completing a 30-min self-paced work trial, and 2) provide test-retest norms specific to athletic women. A retrospective analysis of three heat stress studies was completed using 33 female participants (31±9 y, 54±10 mL min-1 kg-1) that yielded 130 separate trials. Participants were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Women remain underrepresented in the exercise thermoregulation literature and > 70% of studies still do not report ovulatory status or menstrual phase (Hutchins et al 2021). Ovulatory status should not inhibit inclusion into this research topic (Schaumberg et al 2017;Zheng et al 2021b) although, importantly, the current results support calls for future measurement and consideration of ovarian hormone concentrations being standard (Elliott-Sale et al 2021). Individualization of human thermoregulation models improves the prediction of heat strain, largely through an increase in the number of input parameters (Havenith 2001).…”
Section: Perspectives and Significancementioning
confidence: 85%
See 2 more Smart Citations
“…Women remain underrepresented in the exercise thermoregulation literature and > 70% of studies still do not report ovulatory status or menstrual phase (Hutchins et al 2021). Ovulatory status should not inhibit inclusion into this research topic (Schaumberg et al 2017;Zheng et al 2021b) although, importantly, the current results support calls for future measurement and consideration of ovarian hormone concentrations being standard (Elliott-Sale et al 2021). Individualization of human thermoregulation models improves the prediction of heat strain, largely through an increase in the number of input parameters (Havenith 2001).…”
Section: Perspectives and Significancementioning
confidence: 85%
“…Results reported in the current study were those for which a maximal number of measures were recorded for the n = 36. For interested readers, other physiological (i.e., thermoregulatory, cardiovascular, inflammatory) and reliability measurements were performed during these trials and can be found in our separate studies (Lei et al 2017 , 2019 ; Zheng et al 2021a , 2021b ).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have previously demonstrated when using a similar protocol that a dietary intervention resulted in an attenuated T core response of 0.2 ± 0.5°C during the 45 min fixed-intensity pre-load [ 23 ]. Based on the current results ( Table 2 and Figure 4 ) we can interpret this finding as not only statistically valid but greater than the measurement error; in other words, we can be confident of the true effect of the intervention based on the signal-to-noise ratio [ 24 ]. Secondly, future studies investigating interventions or comparing different populations now have a known measurement error for ΔT core during exercise that can inform sample size justification [ 16 ].…”
Section: Discussionmentioning
confidence: 77%
“…Small data sets (e.g. <40) are more sensitive to heterogeneity [ 12 , 24 ]. Therefore, we caution interpretation of the current results without confirmatory research using larger data sets.…”
Section: Discussionmentioning
confidence: 99%